Дослідження методів оптимізації при розробці програмного забезпечення для планування ресурсів ІТ-проєктів - Ласіцина, Ю. М. (ХНУРЕ, 2023)
Nowadays, enterprise automation is rapidly growing in many industries. This is because customers require information systems to meet increasingly specific business needs. One of the most promising sectors of human activity today is the IT industry. An important element is the execution of numerous IT projects for clients from around the world. Project administration must be well executed to ensure successful completion. The scientific novelty of the obtained results are based on the development of an approach to resource planning that takes into account constraints, risks, and analysis; algorithms for solving the problem are developed and improved through the use of experimental research.